Reimbursement Trends in Pediatric Otolaryngology From 2000 to 2020: A CMS Physician Fee Schedule Analysis. (28th December 2022) - Yaffe, Noah M.; Quereshy, Humzah A.; Quinton, Brooke A.; Otteson, Todd D.; Shah, Jay R.
Abstract: Objective: The aim of this study was to evaluate the financial trends in Medicare reimbursement rates for the most billed procedures at a single institution from 2000 to 2020 within pediatric otolaryngology. Study Design: Retrospective data analysis. Setting: United States. Methods: The most billed surgical and in‐office procedures in pediatric otolaryngology at our institution were identified in the Physician Fee Schedule Look‐up Tool from the Centers for Medicare and Medicaid Services to extract reimbursement data for each CPT code ( Current Procedural Terminology ). Monetary data were adjusted for inflation to 2020 US dollars per the changes to the consumer price index. Mean annual and total percentage changes in reimbursement were calculated by the adjusted values for all included procedures (N = 25). Results: From 2000 to 2020, without adjusting for inflation, reimbursement for the most billed procedures increased by 10.9%, while the allocated relative value unit per procedure increased by 15.4%. However, when adjusted for inflation, reimbursement for these procedures decreased by 27.5% over the study period. Conclusions: The study findings identify a downward trend in reimbursement for the most billed procedures in pediatric otolaryngology at our institution. Given the low predominance of pediatric otolaryngology codes within Medicare reimbursement, these codes are rarely reviewed for accurate revaluation. It is imperative that our professional society remain active and engaged within this process to ensure quality delivery of care to our patients.